An Analytical Approach to the Function of Internal Auditors’ Job Well-Being in Auditor Professional Maturity - Dinyarian, Nooshin; Ramezani, Javad; Fallah, Ali; Khalilpour, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The objective of this study was to develop and validate a comprehensive model of internal auditors’ job well-being and examine its effect on auditor professional maturity. Methods and Materials: This research adopted a mixed-methods design combining qualitative and quantitative approaches. In the qualitative phase, thematic analysis was conducted through semi-structured interviews with expert internal auditors and academic specialists to identify the underlying dimensions of internal auditors’ job well-being. Extracted themes were categorized into overarching, organizing, and basic themes, forming the conceptual framework of the model. In the quantitative phase, data were collected using a researcher-developed questionnaire measuring job well-being dimensions and a standardized instrument assessing auditor professional maturity. The statistical population consisted of internal auditors, and sampling was conducted using purposive selection in the qualitative phase and survey-based sampling in the quantitative phase. The Delphi technique was employed to confirm content validity and expert consensus regarding identified components. Measurement model reliability and validity were evaluated using confirmatory factor analysis, Cronbach’s alpha, composite reliability, convergent validity (AVE), and discriminant validity (Fornell–Larcker criterion). Structural Equation Modeling based on the Partial Least Squares (PLS-SEM) approach was applied to test the research hypothesis and assess model fit. Findings: The structural model demonstrated satisfactory measurement and structural fit indices. Results indicated that internal auditors’ job well-being has a positive and statistically significant effect on auditor professional maturity (β = 0.564, T = 20.226). The model explained approximately 52.9% of the variance in professional maturity. All dimensions of job well-being—including professional satisfaction, growth and development opportunities, social support and communication, psychological and physical health, and enhancement of audit process quality—were validated and significantly contributed to the latent construct of job well-being. Reliability, convergent validity, discriminant validity, and predictive relevance indices confirmed the robustness of the proposed model. Conclusion: The findings indicate that internal auditors’ job well-being functions as a fundamental driver of professional maturity by strengthening psychological readiness, ethical judgment, professional competence, and organizational engagement. Promoting well-being-oriented organizational environments can enhance audit effectiveness, reinforce professional independence, and improve governance quality. The study highlights the strategic importance of integrating human-centered well-being policies into professional auditing frameworks to achieve sustainable professional development.